2012
DOI: 10.1371/journal.ppat.1002557
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Perforin-dependent CD8+ T Cell Immunity for Rapid Protective Vaccination in a Murine Model for Human Smallpox

Abstract: Vaccination is highly effective in preventing various infectious diseases, whereas the constant threat of new emerging pathogens necessitates the development of innovative vaccination principles that also confer rapid protection in a case of emergency. Although increasing evidence points to T cell immunity playing a critical role in vaccination against viral diseases, vaccine efficacy is mostly associated with the induction of antibody responses. Here we analyze the immunological mechanism(s) of rapidly protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 93 publications
(166 reference statements)
4
35
0
Order By: Relevance
“…To explain this prerequisite, we analyzed the infiltration of various cell types at the vaccination site. Kremer et al have reported the massive lung infiltration of monocytes, dendritic cells, neutrophils, and NK cells in the first 6 to 72 h after intranasal vaccination with MVA (39). We could demonstrate a similar scenario 24 to 48 h after subcutaneous injection of MVATG9931: neutrophils, NK cells, as well as macrophages and pDCs assembled around the injection site.…”
Section: Discussionsupporting
confidence: 73%
“…To explain this prerequisite, we analyzed the infiltration of various cell types at the vaccination site. Kremer et al have reported the massive lung infiltration of monocytes, dendritic cells, neutrophils, and NK cells in the first 6 to 72 h after intranasal vaccination with MVA (39). We could demonstrate a similar scenario 24 to 48 h after subcutaneous injection of MVATG9931: neutrophils, NK cells, as well as macrophages and pDCs assembled around the injection site.…”
Section: Discussionsupporting
confidence: 73%
“…In one instance, immunization scheme I -in which priming was performed with peptide formulated with poly(I:C) plus anti-CD40 antibody -resulted in a much more robust TCD8 response against F4L [6][7][8][9][10][11][12][13][14] than that resulting from scheme II. Consequently, the former resulted in much better protection than the latter, which was essentially nonprotective (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, when immunogenic, we also discovered that individual TCD8 specificities, despite similar functional competence, exhibited varied protective efficacy in active VACV infection. Critically, this varied protection was not directly linked to TCD8 frequency elicited by vaccination: e.g., some responders at lower frequency (A3L [192][193][194][195][196][197][198][199][200] ) were more protective than others elicited at higher frequency (F4L [6][7][8][9][10][11][12][13][14], whereas some responders (L4R [37][38][39][40][41][42][43][44][45] were not protective regardless of their frequency. It is likely that differential abundance of determinants and/or kinetics of their natural presentation define visibility of infected cells to cognate TCD8 in vivo, thus restricting protective responses to specificities that efficiently recognize infected cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations